Increasing Speaking Skill through YouTube Video as English Learning Material during Online Learning in Pandemic Covid-19 - Syafiq, Ahmad Nur; Rahmawati, Amalia; Anwari, Anwari; Oktaviana, Tyas (Universitas Lancang Kuning, 2021)
YouTube video is one alternative solution in teaching speaking during pandemic. This study attempts to find the use of YouTube videos to improve speaking skill of students and how teaching and learning process using YouTube videos are implemented in the class. A classroom action research was conducted to first semester college students of Muhammadiyah University of Kudus in 2020. The population of this study was all non-English program and the samples were 85 students in redundant class chosen using purposive sampling. The data were obtained from speaking assessment and interview and later analyzed by using constant comparative method and descriptive statistic. This study showed that YouTube video as English learning material improved speaking skill of students including fluency, vocabulary, pronunciation, grammar, and content. Therefore, it can be concluded that the use of YouTube Video is able to improve the students’ speaking skill during online learning in pandemic Covid-19. Further study may concern on the use of YouTube Video to teach other English skills like reading and writing.